2020
DOI: 10.2147/nss.s236393
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and Risk Factors of Restless Legs Syndrome in Hemodialysis Patients</p>

Abstract: These authors contributed equally to this workObjective: The current study aimed to investigate the prevalence and risk factors of restless legs syndrome (RLS) in patients undergoing hemodialysis, as well as the mortality and risks of cardiovascular and cerebrovascular events. Methods: A total of 354 hemodialysis patients from four hospitals were enrolled. RLS was diagnosed using the International RLS Study Group (IRLSSG) criteria. The patients were evaluated face-to-face using the IRLSSG rating scale, Epworth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…Previous studies have found that the duration of hemodialysis is a risk factor for RLS, and the RLS severity was positively correlated with the duration of dialysis ( 31 , 32 ). Our studies have produced consistent results.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have found that the duration of hemodialysis is a risk factor for RLS, and the RLS severity was positively correlated with the duration of dialysis ( 31 , 32 ). Our studies have produced consistent results.…”
Section: Discussionmentioning
confidence: 94%
“…18) hsCRP is widely used in clinical practice, especially in cerebrovascular disease and CVD. 19) hsCRP is considered as a risk factor of CVD and can increase the mortality of CVD. 20,21) CRP is involved in the pathogenesis and development of vascular inflammation and coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our analysis, we attempted to interpret the results associated with increased CHR and severity of coronary artery stenosis.hs-CRP is a blood biomarker produced by the liver, representing acute systemic in ammation, and is considered a perfect marker for assessing systemic in ammation because its serum level does not change with circadian rhythm within 24 hours and does not change with food intake 12 . hs-CRP is widely used in clinical practice, especially in cerebrovascular and cardiovascular diseases 13 . hs-CRP is considered as a risk factor of cardiovascular diseases and can increase the mortality of cardiovascular diseases 14,15 .…”
Section: Discussionmentioning
confidence: 99%